2012
DOI: 10.1515/1559-0410.1370
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Player Quota, Experience and Efficiency of Basketball Players

Abstract: This study analyzes how the efficiency of basketball players depends on experience, player's nationality and team type. Using data for players in the Turkish Basketball League (TBL) from 1997 to 2010, we first show that efficiency of players initially increase with experience, but after a certain level decrease with it. Second, foreign players are on average more talented than native players. Third, the experience-efficiency link is not valid for foreign players indicating that more experience does not affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Players' experience may be another important factor to be considered in the selection process. Multiple studies have suggested that playing experience is related to performance in team sports (Black, Gabbett, Naughton, & McLean, 2016;Ozmen, 2012;Swann, Keegan, Piggott, & Crust, 2012;Williams & Ford, 2008). In particular, expert players set more specific goals, selected more techniqueoriented strategies, made more strategy attributions, and displayed higher levels of self-efficacy than non-experts and novices (Cleary & Zimmerman, 2001; Kitsantas & Zimmerman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Players' experience may be another important factor to be considered in the selection process. Multiple studies have suggested that playing experience is related to performance in team sports (Black, Gabbett, Naughton, & McLean, 2016;Ozmen, 2012;Swann, Keegan, Piggott, & Crust, 2012;Williams & Ford, 2008). In particular, expert players set more specific goals, selected more techniqueoriented strategies, made more strategy attributions, and displayed higher levels of self-efficacy than non-experts and novices (Cleary & Zimmerman, 2001; Kitsantas & Zimmerman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that lower level teams were more dependent on foreign Guards playing for success compared to national Guards. A possible explanation for this result might be due to the perceived regard of foreign players' ability by coaches and teams [15] and typically greater financial investment in such players [14]. Further, it may be a result of the poorer shooting percentage (% unsuccessful 2-point field-goals) in national players and greater 3-point shooting by foreign players in these clusters (See Table 2), which are key statistics for success in female basketball [3,23].…”
Section: Discussionmentioning
confidence: 99%
“…From a general point of view, the results showed that foreign players have a better performance according to team ability and playing position for most of the performance indicators, with higher values specifically for % minutes played, % successful 2-point field-goal, % successful free-throws, and % assists. These findings will be of extreme importance for coaches and managers when recruiting players based on their performance strengths and weaknesses, their playing position, and nationality [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations